Minorities and Religious Freedom in a Democracy - Massey, James, (Brill | Manohar Publishers & Distributors, 2024)
This book has four parts. Part one explains the place of minorities in a democracy, examines the process of their formation at the global as well as national levels and looks at the response received by them at these forums. Parts two and three deal with basic rights of minorities enshrined in Articles 25 and 30 of the Indian Constitution, the detailed history of these articles, the debates in the Constituent Assembly and other related documents. This book also deals with Christians as a minority and controverts the myth that they are the most forward community. It details the general constitutional rights as well as special rights of the minorities in India and focuses attention on the relationship between human rights and minority rights and the role of National Commission for Minorities in protecting the human rights of minorities. The appendices contain important international and national documents relating to human and constitutional rights of the minorities. An essential reading for sociologists, political scientists, human rights activists and all others interested in the issues involved and the future of Indian polity.